Conflit armé en Ituri et insécurité foncière dans le Territoire de Djugu de 1999 à 2018 - Kumbatulu Bakulu, (IJRDO - Journal of Social Science and Humanities Research, 2019)
Ituri has experienced its share of war and violence, even if it took place in the shadow of the other wars that ravaged the DRC. According to several observers, the 1999 outbreak of violence was directly caused in Ituri by a deep-rooted local conflict, related first to issues of access to land followed by economic opportunities and political power issues. This war was at the root of land insecurity that is currently producing multiple negative phenomena in the territory of Djugu. This article establishes a relationship between war and land insecurity that negatively community cohabitation in Djugu.